Evidence that the Localization of the Elongation Factor Spt16 Across Transcribed Genes Is Dependent Upon Histone H3 Integrity in Saccharomyces cerevisiae - Duina, Andrea A. (Copyright © 2007 by the Genetics Society of America, 2007)
A previous study of histone H3 in Saccharomyces cerevisiae identified a mutant with a single amino acid change, leucine 61 to tryptophan, that confers several transcriptional defects. We now present several lines of evidence that this H3 mutant, H3-L61W, is impaired at the level of transcription elongation, likely by altered interactions with the conserved factor Spt16, a subunit of the transcription elongation complex yFACT. First, a selection for suppressors of the H3-L61W cold-sensitive phenotype has identified novel mutations in the gene encoding Spt16. These genetic interactions are allele specific, suggesting a direct interaction between H3 and Spt16. Second, similar to several other elongation and chromatin mutants, including spt16 mutants, an H3-L61W mutant allows transcription from a cryptic promoter within the FLO8 coding region. Finally, chromatin-immunoprecipitation experiments show that in an H3-L61W mutant there is a dramatically altered profile of Spt16 association over transcribed regions, with reduced levels over 5′-coding regions and elevated levels over the 3′ regions. Taken together, these and other results provide strong evidence that the integrity of histone H3 is crucial for ensuring proper distribution of Spt16 across transcribed genes and suggest a model for the mechanism by which Spt16 normally dissociates from DNA following transcription.